MODEL OF SPREAD CONTENT DISEASE FOR ASSOCIATION OF VACCINE - Jumiati, Ety; Husein, Ismail (UIN Sumatera Utara, 2018)
Transmission of infectious diseases in epidemiological models is usually based on the assumption that populations in random mixing. However, in reality this assumption is not fulfilled, because each individual has a limited set of contacts that they can pass through infection; the ensemble of all such contacts forms a complex network. Knowledge of network structure allows a model to calculate the dynamics of an epidemic at a population scale from individual level infection behavior. This paper discusses mathematical models to illustrate the epidemic pattern of transmission of infectious diseases in dynamic networks based on compartment systems.